Armor Piercing Projectiles Based on Depleted Uranium and the Consequences of Their Use for the Environment and People - M. V. Supotnitskiy (Вестник войск РХБ защиты, 2023)
The intention of the collective West to supply the armed forces of Ukraine with armor-piercing shells with cores (penetrators) made of depleted uranium (DU), is changing the situation in the zone of special military operation (SVO). A new damaging factor is introduced into combat operations – uranium-238 (238U), one of the longest-lived natural radioactive isotopes of uranium.   The purpose of the review is to identify the signs and consequences of the use of armor-piercing projectiles based on depleted uranium.   Materials and research methods. The sources available through the PubMed, Google Scholar and Russian Electronic Library databases were analyzed.   Research results. NATO uses DU in 20-, 25-, 30-, 105-, 120- and 140-mm caliber projectiles. The cores are made from recycled DU, which is a waste from the production of nuclear weapons. Due to man-made isotopes, it is more radioactive than DU from natural uranium. When such a projectile hits an armored object, a large amount of respirable radioactive and toxic dust of black uranium oxides, small fragments and fragments of the penetrator, remaining in the armored vehicles and around it, is formed. One 120 mm projectile produces approximately 950 g of black dust. Almost 99 % of the internal dose received by the military will come from alpha particles, the most dangerous to health. Projectiles that miss their targets sink deep into the soil, their penetrators corrode for decades, releasing soluble uranium compounds into underground water sources. In areas where DU shells were used, mass diseases of «unexplained etiology» are observed among military personnel and civilians, reducing their life expectancy and fertility.   Discussion of results and conclusions. The first signs of the use of shells with DU, which can be installed on the battlefield: round holes in the armor of tanks and the presence of solid black dust around them and in the tank itself. In case of fires in the warehouses of such shells, due to other oxidation conditions, crumbling yellow dust is formed. When examining it, it is necessary to pay attention to the presence of elevated concentrations of 236U. The fact that a soldier was hit by DU can be confirmed by the presence of uranium in his urine. The use of DU shells on the territory of the Russian Federation, in terms of its consequences for people and nature, is the use of radiological weapons, a disguised form of nuclear warfare. And it must be treated accordingly.